ELETROCATALISADORES À BASE DE Fe,Co(10%m)-N(PAR,PAN)/C(500-900 ºC) PARA A REDUÇÃO DO OXIGÊNIO MOLECULAR - Carvalho, Dayvid Pires (2014)
In order to develop a new Pt-free reducing agents for oxygen reduction reaction (ORR), the ligands 1 - (2-Pyridylazo)-2-naphthol (PAN) and 4-(2-pyridylazo)-resorcinol (PAR) were studied as nitrogen sources complexing with Fe (II) and Co (II) ions, supported on carbon nanoparticles (10 wt. % metal loading) and heat treated at temperature of 500, 700 and 900°C. The synthesized complexes ([ML₂]; M²⁺= Fe, Co; L = PAN, PAR) were characterized by UVVis and Infrared spectroscopies before impregnation step. By cyclic voltammetric technique it was found that all eletrocatalysts showed an increase of performance for ORR after heat treated and that the highest efficiency were reached by: Fe-PAN/C -700°C (0,818 V x ENH), Fe-PAN/C- 900 °C (0,786V x ENH), Co-PAN/C - 500 °C (0,657V x ENH) e Co-PAN/C - 700°C (0.673 V x ENH), e Co-PAN/C - 900°C (0.612 V x ENH), Co-PAR/C - 700°C (0.588 V x ENH), Co-PAR/C - 900°C (0.623 V x ENH) e Fe-PAR/C - 700°C (0.598 V x ENH). With EDR studies, it was possible to calculate, with Koutecký Levich equation, the number of electrons involved in the ORR for each catalyst at potentials of 0.1, 0.2, 0.3 and 0.4 V. Except COPAR-700 °C which the adopted method did not allow the the number of electrons, the other catalysts, which were calculated were nearer the behavior of a mechanism via 2 and 4e- while others saw.